MEKANISME PENYELESAIAN SENGKETA NASABAH ASURANSI MELALUI LEMBAGA ALTERNATIF PENYELESAIAN SENGKETA JASA KEUANGAN (LAPS SJK) - M Alfarizzi Nur (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
The insurance business entity has failed to pay for the disbursement of the policy. For example, Bumiputera customers are currently still waiting for insurance policy disbursements. Alternative institution For financial services sector dispute resolution is here to assist in resolving the insurance dispute by offering non-litigation settlement efforts. This research was carried out in a normative-juridical manner by reviewing the applicable laws and regulations along with the principles, theories, and doctrines of the experts. To support the research, literature study materials relevant to the subject matter of this study will be included. The results of this study indicate that the alternative institution financial services has mediation and arbitration services in dispute resolution. The mediation will be attended by the customer and the insurance business entity as well as a third party as a mediator. Successful mediation with a peace agreement will be outlined in a peace deed. Arbitration is a dispute resolution model agreed upon by both parties before or after a dispute occurs. The arbitrator as a third party is a panel of judges appointed by the parties to the dispute or management. The arbitration award is final and binding.